Factores estructurales asociados a la productividad de las microempresas moviliarias de la parroquia rural Valle Hermoso en la provincia de Santo Domingo de los Tsáchilas. - Huang Flores, Verónica Gabriela Urgilés Monar, Michelle Verónica (2020)
This research project focuses on the research of the association between the Structural Factors and the Productivity of the micro-enterprise furniture sector of the Valle Hermoso rural parish. A review of relevant theoretical foundations was carried out to identify the structural factors that are: Product market structure, innovation, workforce, structural design, manufacturing system, personnel management and marketing-communication as well as determining the elements that It has productivity in wood sector, these being: quality, raw material, manufacturing and marketing processes, which are detailed by limiting productivity within the furniture sector, so that a clear understanding of the treated being points is obtained, and thus be able to correlate with the structural factors. The focus of this research is quantitative since it uses data collection and statistical analysis in order to establish the behavior of the variables, the research type is bibliographic and field with a correlational purpose with it was possible to determine the association degree of two research variables. For information gathering, a survey was applied that was analyzed and reviewed by an expert judgment such as the readers and corresponding tutor, which consisted of 26 questions and that were made to the owners of the five furniture for the research work in order to know what factors and processes applied to furniture stores manufacturing; Thanks to the obtained results analysis through the SPSS statistical tool, it was possible to observe which of the variables are associated and which one are not by Pearson's correlation highlighting the most significant relationships and in this way the conclusions and recommendations were made according to the established objectives. This research work is proposed as a guideline for other studies related to this topic in addition to the furniture sector it can be introduced in other sectors with similar characteristics.